Diễn văn bế mạc Đại hội đại biểu toàn quốc lần thứ IV của Đảng do Tổng Bí thư Lê Duẩn đọc ngày 20/12/1976 (1976)
Diễn văn bế mạc Đại hội đại biểu toàn quốc lần thứ IV của Đảng do Tổng Bí thư Lê Duẩn đọc ngày 20/12/1976